Peningkatan Kompetensi Pedagogik Guru dalam Menyusun RPP Melalui Supervisi Akademik di SD Negeri 08 Talang Muandau - Kuraesin Kuraesin (Journal on Education, 2022)
This study aims to obtain information and discuss the improvement of teacher pedagogic competence in preparing lesson plans through academic supervision at SD Negeri 08 Talang Muandau. This type of research is School Action Research (PTS). This research was conducted at SD Negeri 08 Talang Muandau. This research was conducted in the odd semester of the 2022/2023 academic year, which began in July 2022. The subjects in this study were all 5 teachers at SD Negeri 08 Talang Muandau. The research procedure consisted of two cycles with four stages of research, namely planning, implementation, observation and reflection. Data collection techniques in this study were interviews, observation, and discussion. The collected data were analyzed using the percentage formula. The results showed that through the implementation of academic supervision can improve the pedagogic ability of teachers in preparing lesson plans at SD Negeri 08 Talang Muandau.